Pembuatan Direktori Informasi Wilayah Sungai Indragiri-Akuaman di Kementerian Pekerjaan Umum dan Perumahan Rakyat Direktorat Jendral Sumber Daya Air Balai Wilayah Sungai Sumatera V - Fariza, Nurul; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The aim of this research is (1) designing and regenerating a printed directory or in the form of directory book which can be brought to gain infromation aboutÂ Â Â Indragiri-Akuaman river tourism guides in Kementerian Pekerjaan Umum dan Perumahan Rakyat Direktorat Jendral Sumber Daya Air Balai Wilayah Sungai Sumatera V, 2) describing the geographical condition of the Indragiri-Akuaman river region as well as possible, (3) to give solution from the writer's limitation and effort that arised through the limitation of research in making information directory of Indragiri-Akuaman river area at Kementerian Pekerjaan Umum dan Perumahan Rakyat Direktorat Jendral Sumber Daya Air Balai Wilayah Sungai Sumatera V. Data is collected through observation and interviews with the parties of Unit Sisda (water resources information system). Data collection is conducted descriptively. Keyword : directory information, Indragiri-Akuaman river